Development of a new approach for high-quality quadrupling frequency optical millimeter-wave signal generation without optical filter - Nael A., Al-Shareefi; Syed I., S. Hassan; Mohd Fareq, Abd Malek, Dr.; Razali, Ngah, Assoc. Prof. Dr.; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Rashid Ali, Fayadh; Jaafar Adhab, ALdhaibani; Hasliza, A. Rahim (PIER, 2013)
Link to publisher's homepage at http://www.jpier.org/PIER/